2015
DOI: 10.1016/j.fertnstert.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Female exposure to phenols and phthalates and time to pregnancy: the Maternal-Infant Research on Environmental Chemicals (MIREC) Study

Abstract: Elevated TCS exposure may be associated with diminished fecundity. BPA and phthalates showed no negative impact; on the contrary, some phthalates might be associated with a shorter time to pregnancy. A major limitation of the study was that only one measurement of exposure was available for each woman after conception. Further research is necessary to test these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 61 publications
5
93
1
2
Order By: Relevance
“…Similar problems with attempting a PI(E)CO review can be observed with the two available studies on exposure to TCS and time to pregnancy (Velez et al 2015;Smarr et al 2017). The results from these studies were inconsistent, as were the study design and exposure assessment approaches.…”
Section: Consistency Of Methods Results and Reporting Across Studiesmentioning
confidence: 75%
See 4 more Smart Citations
“…Similar problems with attempting a PI(E)CO review can be observed with the two available studies on exposure to TCS and time to pregnancy (Velez et al 2015;Smarr et al 2017). The results from these studies were inconsistent, as were the study design and exposure assessment approaches.…”
Section: Consistency Of Methods Results and Reporting Across Studiesmentioning
confidence: 75%
“…While we did not formally assign quality tiers for steps taken to avoid sample contamination and to ensure analyte stability, we note that only two studies specifically reported the incorporation of field and lab blanks in their methods (Velez et al 2015;Ashley-Martin et al 2016). None of the studies offered documentation of analyte stability.…”
Section: Exposure Assessmentmentioning
confidence: 98%
See 3 more Smart Citations